Investor Information, Long-Run Risk, and the Term Structure of Equity - Croce, Mariano M.; Lettau, Martin; Ludvigson, Sydney C. (Review of Financial Studies, 2015)
We study the role of information in asset-pricing models with long-run cash flow risk. When investors can distinguish short- from long-run consumption risks (full information), the model generates a sizable equity risk premium only if the equity term structure slopes up, contrary to the data. In general, the short- and long-run components are unidentified. We propose a sparsity-based bounded rationality model of long-run risk that is both parsimonious and fully identified from historical data. In contrast to full information, the model generates a sizable market risk premium simultaneously with a downward-sloping equity term structure, as in the data.